Sharī‘ah Analysis of Acquisition of House Financing Portfolio: A Case Study of Bank Islami and Citi Bank Pakistan - Muhammad Asghar Shahzad; Syed Kashif Saeed; Asim Ehsan (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose - The Objective of this study is to provide a comprehensive scenario of the Acquisition of House Financing transaction taken place between Bank Islami and Citi Bank during 2010 in the light of Sharī’ah guidelines. The purpose of this whole complex transaction was to acquire Citi Banks house financing portfolio. The successful completion of such a transaction is an important milestone for Islamic Banking. The complete understanding of such transactions is of prime importance for Islamic banking academia. Findings - The study concludes that the transaction based on Hawalah (assignment of debt) and Wakalah Lil Qabz (recovery agency) is very complex and intelligently designed to conduct these transactions. Policy Implications - This study will enable the policymakers, Sharī’ah Advisors, and bankers to explore new avenues for investment in Islamic Banking Institutions. This study will also enable academicians and research students to conduct research for product development in related areas with conventional banks. The complete understanding of such transactions is of prime importance for the product development department of Islamic Banks.